The spotted cleaner shrimp, Periclimenes yucatanicus (Ives, 1891), on an unusual scleractinian host - González Muñoz, Ricardo Enrique (2019)
The spotted cleaner shrimp, Periclimenes yucatanicus (Ives, 1891), forms symbioses with sea anemones that may serve as cleaning stations for reef fishes [1]. This Caribbean palaemonid shrimp has usually been reported in symbiotic association with several species of actiniarian hosts, such as Condylactis gigantea (Weinland, 1860) and Bartholomea annulata (Le Sueur, 1817), or even with some corallimorpharians and a scyphozoan jellyfish [2]. During a field survey at Alacranes coral reef (26 June 2016; 2227.14? N, 8945.79? W; 13 m depth) on the Campeche Bank, Yucatán Peninsula, México, two spotted shrimps were observed swimming and walking above the polyps of the head coral Montastraea cavernosa (Linnaeus, 1767). Because none of the usual hosts of P. yucatanicus were detected nearby, we hypothesize that the shrimps were using the scleractinian coral as a host. Some other shrimp species commonly associated with actiniarians were previously reported to be living on stony corals, such as Ancylomenes holthuisi (Bruce, 1969) on Heliofungia actiniformis (Quoy and Gaimard, 1833) in New Guinea [3], and Periclimenes rathbunae Schmitt, 1924 on Dendrogyra cylindrus Ehrenberg, 1834 in Curaçao [4]. The observation (see Figure 1) of Montastraea cavernosa hosting Periclimenes yucatanicus is the second report of a palaemonid shrimp in association with a scleractinian coral in the Atlantic Ocean. The ecological implications of this association are unknown but could be related to a low local availability of usual hosts.